1,3,6-Trihydroxy-7-methoxy-2,8-bis(3-methylbut-2-enyl)-9H-xanthen-9-one - Ee, Gwendoline Cheng Lian; Mohamed Tahir, Mohamed Ibrahim; Silong, Sidik; Wei, Chung Sim; Huey, Chong Kwong (International Union of Crystallography, 2010)
The title compound (trivial name α-mangostin), C24H26O6, isolated from Cratoxylum glaucum, is characterized by a xanthone skeleton of three fused six-membered rings and two 3-methylbut-2-enyl side chains. The three rings in the structure are nearly coplanar, with an r.m.s. deviation for the tricyclic ring system of 0.0014 Å. The two 3-methylbut-2-enyl side chains are in (+)-synclinal and (-)-anticlinal conformations. Intramolecular O—H[cdots, three dots, centered]O and C—H[cdots, three dots, centered]O interactions occur. The crystal structure is stabilized by intermolecular O—H[cdots, three dots, centered]O, C—H[cdots, three dots, centered]O and C—H[cdots, three dots, centered]π interactions.